Konstitusionalisme HAM Indonesia: Dinamika Pengaturan HAM Indonesia Pasca-Amandemen UUD 1945 - Udiyo Basuki (Supremasi Hukum: Jurnal Kajian Ilmu Hukum, 2012)
The constitution was born from constitutionalism which provides limits of state power in one side and guarantee for the rights of people through constitutional provisions in another side. The Constitution is where all legislation must depend. The concept ofthe modern state requires the existence of democracy, rule of law and protection of human rights. A nation, Indonesia has many in the administration of his state of human rights instruments, including the three who had valid constitution, theConstitution of 1945, the Constitution of 1949 United Republik of Indonesia and Provisional Constitution of 1950. The last decade, the 1945 Constitution has undergone four amendments. This paper is going to examine how the effect of amending the Constitution is the dynamics of the settings in which human rights and in other legislation.